Philosophical and pedagogical foundations for developing moral consciousness and education among youth in the context of digital transformation - Mamajonova, Gulnoza (The Lingua Spectrum, 2025)
This article explores the philosophical and pedagogical foundations for developing moral consciousness and education among youth in the era of rapid digital transformation. The study analyzes how digital technologies and communication tools affect young people’s values, social responsibility, and worldview, emphasizing both the opportunities and ethical challenges of the digital environment. It highlights the interrelation between digital literacy and moral education, examining how the concept of “digital citizenship” can foster moral culture and civic responsibility